2016
DOI: 10.1080/16078055.2015.1126759
|View full text |Cite
|
Sign up to set email alerts
|

Development of the serious and casual leisure measure

Abstract: The aim of this study is to test if there are different qualities of serious leisure in a Turkish sample and to develop a valid and reliable serious and casual leisure measure (SCLM) using data from both casual and serious leisure participants. With the use of focus groups, an expert panel, a pilot study, exploratory and confirmatory factor analysis, a 9-factor model with 42 items demonstrated acceptable fit and reliability values. Besides six dimensions of serious leisure set out by Stebbins [(1982). Serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
8
0
5
Order By: Relevance
“…In particular, the concept of serious leisure has been the major focus of the following studies. When the studies are examined it has been shown that some research focused on the development of serious leisure scales (Gould et al, 2008;Munusturlar-Akyıldız and Argan, 2016), some studies took the elder people into the sample within the context of hobby and sports competitions (Brown et al, 2008;Heo et al, 2012Heo et al, , 2013Cheng et al, 2017) and some others delved into exploring serious characteristics of sports competitions, adventure events, dance events, and sport tourism (Jones, 2000;Gibson et al, 2002; • Personal growth…”
Section: Well-being and Stebbins's Theory Of Casual Versus Serious Lementioning
confidence: 99%
“…In particular, the concept of serious leisure has been the major focus of the following studies. When the studies are examined it has been shown that some research focused on the development of serious leisure scales (Gould et al, 2008;Munusturlar-Akyıldız and Argan, 2016), some studies took the elder people into the sample within the context of hobby and sports competitions (Brown et al, 2008;Heo et al, 2012Heo et al, , 2013Cheng et al, 2017) and some others delved into exploring serious characteristics of sports competitions, adventure events, dance events, and sport tourism (Jones, 2000;Gibson et al, 2002; • Personal growth…”
Section: Well-being and Stebbins's Theory Of Casual Versus Serious Lementioning
confidence: 99%
“…The confirmatory factor analysis validated the tool according to the specified criteria (RMSEA = 0.51; CFI = 0.98; NFI = 0.98; NNFI = 0.98; SRMR = 0.56; AGFI = 0.88; GFI = 0 , 89). It seems that serious and casual leisure measure (SCLM) is a valid and reliable tool to measure the level of participation to leisure as serious and casual leisure (Akyıldız Munusturlar & Argan, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Para la elaboración del cuestionario se revisaron constructos que tuviesen directa relación entre surf y ocio serio, (Cheng y Tsaur, 2012;Barbieri y Sotomayor 2013;Tien-ming Cheng y Chiang-Chuan Lu, 2015;Portugal, et al,. 2017), así como otros que relaciona al ocio serio y los atributos propuestos (Hill, y Abbott, 2009;Gómez Varela, 2008;Munusturlar y Argan, 2016;Gould, et al,. 2008;Losier, et al,.…”
Section: Metodologíaunclassified